SYLVIUS: A multimodal and multidisciplinary platform for epilepsy surgery. (May 2021) - Higueras-Esteban, Alfredo; Delgado-Martínez, Ignacio; Serrano, Laura; Principe, Alessandro; Pérez Enriquez, Carmen; González Ballester, Miguel Ángel; Rocamora, Rodrigo; Conesa, Gerardo; Serra, Luis
Highlights: Efficient transfer of information among epileptologists and neurosurgeons. Scenegraph-based processing pipeline to drive registration of multiple datasets. Graphics processing unit (GPU) based detection of vessels for a planned trajectory. Specialized DWI tractography tools for SEEG. Semi-automatic electrode segmentation tool. Abstract: Background and objective: We present SYLVIUS, a software platform intended to facilitate and improve the complex workflow required to diagnose and surgically treat drug-resistant epilepsies. In complex epilepsies, additional invasive information from exploration with stereoencephalography (SEEG) with deep electrodes may be needed, for which the input from different diagnostic methods and clinicians from several specialties is required to ensure diagnostic efficacy and surgical safety. We aim to provide a software platform with optimal data flow among the different stages of epilepsy surgery to provide smooth and integrated decision making. Methods: The SYLVIUS platform provides a clinical workflow designed to ensure seamless and safe patient data sharing across specialities. It integrates tools for stereo visualization, data registration, transfer of electrode plans referred to distinct datasets, automated postoperative contact segmentation, and novel DWI tractography analysis. Nineteen cases were retrospectively evaluated to track modifications from an initial plan to obtain a final surgical plan, using SYLVIUS. Results: The software was used to modify trajectories in all 19 consulted cases, which were then imported into the robotic system for the surgical intervention. When available, SYLVIUS provided extra multimodal information, which resulted in a greater number of trajectory modifications. Conclusions: The architecture presented in this paper streamlines epilepsy surgery allowing clinicians to have a digital clinical tool that allows recording of the different stages of the procedure, in a common multimodal 2D/3D setting for participation of different clinicians in defining and validating surgical plans for SEEG cases.